Motivasi usaha sebagai mediator hubungan antara perilaku inovatif dan kreativitas terhadap keberhasilan usaha pengusaha batik tulis di Kabupaten Kebumen - Azizah, Siti Nur; Ma’rifah, Diana (Faculty of Economics and Business Universitas Jenderal Soedirman, 2017)
Purpose: This study aims to analyze the influence of innovative behavior and creativity on business success mediated by business motivation. Methodology: Respondents in this research were batik entrepreneurs in Kebumen Regency. The number of samples tested is 58 people and data analysis used Partial Least Square (PLS) test. Findings: The results show that creativity has an effect on motivation and business success, and motivation mediates the relationship between creativity and business success. However, innovative behavior has no effect on motivation or business success. So, motivation does not mediate the relationship between innovative behavior and business success. Keywords: business success, business motivation, creativity, innovative behavior, painted batik.